Correlates of Disability in Asian Patients With Major Depressive Disorder - Eurviriyanukul K. (2017)
© 2015 Wiley Periodicals, Inc. PURPOSE: To examine correlates of disability in Asian patients with major depressive disorder (MDD). DESIGN AND METHODS: Participants were outpatients with DSM-IV MDD. Global disability and three disability domains (i.e., work/school, social life/leisure, and family/home life) were key outcomes. Several socio-demographic and clinical characteristics were determined for their associations with disability. FINDINGS: The sample was 493 MDD patients. Apart from the number of hospitalizations, the global disability was significantly associated with depression severity, fatigue, physical health, and mental health. Several clinical but only few socio-demographic characteristics associated with the other three disability domains were similar. PRACTICE IMPLICATIONS: Disability among Asian patients with MDD correlates with the severity of psychiatric symptoms and the hospitalizations due to depression. Socio-demographic characteristics have little impact on the overall disability.